Comparison of basic photosynthetic characteristics between exotic invasive weed Solidago canadensis and its companion species - HU Tian-yin; FANG Fang; GUO Shui-liang; JIANG Hua-wei (浙江大学学报. 农业与生命科学版, 2007)
Photosynthetic indices of Solidago canadensis and its companion species were determined using LCA-4 portable photosynthesis and transpiration system (ADC, England). Results were as follows: (i) The actual maximal net photosynthetic rate of S. canadensis is 19.22 μmol CO2 ·m-2·s-1, lower than those of Erigeron annuus, Conyza bonariensis, Conyza canadensis, but higher than those of Lantana camara, Alternathera philoxeroides, Plantago virginica and Sonchus oleraceus; (ii) During the last ten-day period of May, the daily course patterns of net photosynthetic rates of S. canadensis was characterized by its weak double-peak type, similar to that of Alternanthera philoxeroides; (iii) The light compensation point of S. canadensis was 48.36 μmol·m-2·s-1, revealing its well-adapted to sunny environments; (iv) For S. canadensis, under leaf photosynthetic active radiation (PAR) of 1300-1800 μmol·m-2·s-1 and PAR of 300-400 μmol·m-2·s-1, the net photosynthetic rates of middle leaves are higher than those of the upper leaves and the basal leaves, while under PAR of 15-45 μmol·m-2·s-1, the basal leaves had higher net photosynthetic rates than the middle and upper leaves, which indicates that the basal leaves have lower light compensation point and could more effectively absorb weak light; (v) Compared with those in shady environments, the individuals of S. canadensis in sunny environments increased fast in the plant height and leaf number because of their higher net photosynthetic rates. Additionally, the individuals of S. canadensis in the shady environment have higher total chlorophyll content than those in sunny environment; (vi) According to the correlation coefficients with the net photosynthetic rate, in the sunny environment, the environmental variables influencing the net photosynthetic rate of S. canadensis rankes as leaf photosynthetic active radiation, leaf transpiration rate and leaf temperature; while in the shady environment, the environmental variables ranks as leaf photosynthetic active radiation, relative humidity, transpiration rate and stomatic conductivity.